Henoch-Schönlein Purpura with Adalimumab Therapy for Ulcerative Colitis: A Case Report and Review of the Literature - Joseph J. LaConti; Jean A. Donet; Jeong Hee Cho-Vega; Daniel A. Sussman; Dana Ascherman; Amar R. Deshpande (Case Reports in Rheumatology)
Tumor necrosis factor-α (TNFα) inhibitor therapy has signified an important milestone in the fight against many rheumatological disorders and inflammatory bowel disease (IBD). Cutaneous adverse events caused by this class of medications are well known but relatively uncommon. Most reactions are mild and rarely warrant treatment withdrawal. Henoch-Schönlein purpura (HSP) is a disease with cutaneous vasculitis, arthritis, and gastrointestinal and renal involvement that is usually seen in children, though the worst complications are typically seen in adults. We present a case of HSP complicating adalimumab treatment in a patient with ulcerative colitis who had achieved endoscopic remission. We review similar cases reported in the literature and discuss the consequences of these autoimmune diseases.